Migration and Economic Development in Kosovo - World Bank (Washington, DC, 2013)
Kosovo has one of the largest international migration flows in the world. Much emigration has been for economic reasons and to escape armed conflict in the late 1990s; resolution of the conflict does not appear to have offered migrants enough incentive to return. Even though migration slowed with the global economic crisis, a reported 3.5 percent of the working population aged 15 and above have expressed interest in emigrating in the next 12 months. The first objective of this study is to illustrate the importance of migration and remittances for Kosovo, drawing on data from recent surveys. The second is to identify policies implemented in other countries that the Kosovan authorities might find useful for maximizing the benefits from its large migrant population. The study does not specify policies the Kosovan authorities should adopt; instead, it sets out policies and instruments the authorities could consider if they wish to more tightly link migration to development. The study has two parts. The first describes migration and remittances trends in Kosovo and links them to labor outcomes, poverty, and investment. The second presents migration policies other countries have introduced, including some countries that are, like Kosovo, small, post-conflict, developing countries with a large diaspora in developed countries.